Seizures regulate the cation-Cl− cotransporter NKCC1 in a hamster model of epilepsy: implications for GABA neurotransmission - Bonet-Fernández, Juan-Manuel; Tranque, Pedro; Aroca-Aguilar, Jose Daniel; Muñoz, Luis J.; López, Dolores E.; Escribano, Julio; de Cabo, Carlos (Frontiers in Neurology, 2023)
Background: The balance between the activity of the Na+/K+/Cl- cotransporter (NKCC1) that introduces Cl- into the cell and the K+/Cl- cotransporter (KCC2) that transports Cl- outside the cell is critical in determining the inhibitory or excitatory outcome of GABA release. Mounting evidence suggests that the impairment of GABAergic inhibitory neurotransmission plays a crucial role in the pathophysiology of epilepsy, both in patients and animal models. Previous studies indicate that decreased KCC2 expression is linked toaudiogenic seizures in GASH:Sal hamsters, highlighting that Cl- imbalance can cause neuronal hyperexcitability. In this study, we aimed to investigate whether the Na+/K+/Cl- cotransporter NKCC1 is also affected by audiogenic seizures and could, therefore, play a role in neuronal hyperexcitability within the GASH:Sal epilepsy model. Methods: NKCC1 protein expression in both the GASH:Sal strain and wild type hamsters was analyzed by immunohistochemistry and Western blotting techniques. Brain regions examined included cortex, hippocampus, hypothalamus, inferior colliculus and pons-medulla oblongata, which were evaluated both at rest and after sound-inducing seizures in GASH:Sal hamsters. A complementary analysis of NKCC1 gene slc12a2expression was conducted by real-time PCR. Finally, protein and mRNA levels of glutamate decarboxylase GAD67were measured as an indicator of GABA release. Results: The induction of seizures caused significant changes in NKCC1 expression in epileptic GASH:Sal hamsters, despite the similar brain expression pattern of NKCC1 in GASH:Sal and wild type hamsters in the absence of seizures. Interestingly, the regulation of brain NKCC1 by seizures demonstrated regional specificity, as protein levels exclusively increased in the hippocampus and hypothalamus. Complementary real-time PCR analysis revealed thatNKCC1 regulation was post-transcriptionalonly in the hypothalamus. In addition, seizures also modulated GAD67 mRNA levelsin a brain region-specific manner. The increased GAD67 expression in hippocampus and hypothalamus of the epileptic hamster brain suggests that GABA release during seizures overlaps with NKCC1 upregulation in these regions. Conclusions: Our results indicate that seizure induction causes dysregulation ofNKCC1 expression in GASH:Sal animals, which overlaps with changes in GABA release. These observations provide evidence for the critical role of NKCC1 in how seizures affect neuronal excitability, and support NKCC1 contribution to the development of secondary foci of epileptogenic activity.